Hamstring injury prevention practices and compliance of the Nordic hamstring program in English professional football - Chesterton, P.; Tears, C.; Wright, M.; Portas, M. (Translational Sports Medicine, 2021)
The Nordic Hamstring exercise program (NHP) is an evidence-based injury prevention protocol. The aims of this study were to (a) report professional English football clubs' practices of hamstring injury prevention strategies, (b) identify the NHP implementation in English football, and (c) understand reasons for the NHP's inclusion or exclusion. An electronic survey was completed by 53 of 91 (58%) English professional football clubs. Forty-three clubs had a formal hamstring injury prevention program with the NH exercise (95%), eccentric strength exercises (93%), and functional training (81%) the most common methods utilized. Twenty clubs (38%) implemented the NHP, but only 9 (17%) completed the full program and were classed as compliant. Respondents partially agreed (Mean 3.92 ± SD 0.87) the NHP could substantially reduce injuries in football and would be effective at their own club (3.77 ± 0.72). Participants partially agreed the exercise caused muscle soreness (3.90 ± 0.85). Barriers to wider implementation included players not positively perceiving the program (79%) and resulting muscle soreness (60%). 57% believed a cultural shift was required to increase compliance. Medical professionals within English football value the injury prevention role of the NHP. A cultural shift would be required mainly from players to allow successful implementation.